Metal doped keratin film standard for LA-ICP-MS determination of lead in hair samples - Pracha Cheajesadagul (2018)
Lead doped keratin film standard was introduced as a new calibration standard for LA-ICP-MS determination of Pb along hair strands. The Pb doped keratin film standard was prepared by precipitation of hair protein solution casting in Pb standard solutions in the presence of trichloroacetic acid as a denaturant solution. Sulfur, which is a major matrix element in hair, was used as an internal standard element to normalize Pb intensity and to correct for variations in ablation efficiency and plasma condition. The method was applied to quantitatively determine Pb distribution along a single human hair strand obtained from workers in a battery manufacturing factory in Thailand who faced risk of Pb exposure. Single hair strands were analyzed along their length by LA-ICP-MS with a fixed spot size of 50 μm. The position of an analyzed hair sample on a strand was converted into time (hair closer to the scalp is newer) on the basis of an average hair growth rate of 0.33 mm per day. The patterns of Pb distribution of each worker in the same battery factory were different suggesting that these workers might either not be involved in the same activities or not work in the same room. This study demonstrated the applicability of LA-ICP-MS for rapid acquisition and tracking Pb concentrations along a single hair strand. © 2011 The Royal Society of Chemistry.